1973
DOI: 10.1073/pnas.70.10.2837
|View full text |Cite
|
Sign up to set email alerts
|

A New Concept for Energy Coupling in Oxidative Phosphorylation Based on a Molecular Explanation of the Oxygen Exchange Reactions

Abstract: The Pi z HOH exchange reaction of oxidative phosphorylation is considerably less sensitive to uncouplers than the Pi T ATP and ATP ;± HOH exchanges. The uncoupler-insensitive Pi 2. HOH Previous findings have shown that the Pi T HOH exchange is less sensitive to 2,4-dinitrophenol than the Pi T. ATP exchange or the capacity for net oxidative l)hosphorylation (10)(11)(12). However, the significance or the source of this exchange has not been known. The possibility exists that it might reflect activities of enzy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
151
2
5

Year Published

1975
1975
2017
2017

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 334 publications
(165 citation statements)
references
References 20 publications
7
151
2
5
Order By: Relevance
“…In 1973, Boyer [13] and Slater [14] suggested that the energy for ATP synthesis is required not for the esterification of ADP by phosphate per se but for the dissociation of ATP. This postulate is now strongly supported by the following evidence.…”
Section: First Modification Of the Chemiosmotic Hypothesis: For The Ementioning
confidence: 99%
“…In 1973, Boyer [13] and Slater [14] suggested that the energy for ATP synthesis is required not for the esterification of ADP by phosphate per se but for the dissociation of ATP. This postulate is now strongly supported by the following evidence.…”
Section: First Modification Of the Chemiosmotic Hypothesis: For The Ementioning
confidence: 99%
“…That such conformation changes might be coupled to covalent bond formation in muscle or mitochondria was suggested a decade ago [21]. More recently, the concept has been sharpened to suggest that ATP synthesis is driven by conformationally-linked changes in the affinity for reactants at the catalytic site [ 14,15,22,23]. These affinity change&could readily allow conformational energy to be used for covalent bond formation.…”
Section: Energy Transduction Through Protein Conformation Changesmentioning
confidence: 99%
“…The actual conversion of bound ADP and Pi into ATP is regarded as proceeding without direct coupling to an energy supply. Important evidence suggesting this concept is based on the observation [10][11][12][13][14][15] that submitochondrial particles catalyze an oligomycin-and/or DCCD-sensitive, uncoupler-insensitive exchange of oxygen between Pi and H20 accompanying the formation of Pi from ATP ('intermediate Pi "~ HOH exchange'). Based on detailed studies of this exchange reaction [17,18] an alternating catalytic site mechanism was recently formulated [18], according to which an energy-requiring conformational change of F1 [21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Evidence accumulated in recent years suggests that the mitochondrial ATPase F~ (and similar ATPases of chloroplasts and bacteria) can undergo energy-linked conformational changes that may be intrinsically involved in ATP synthesis coupled to electron and proton transport [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. It has been proposed [ 12,[15][16][17] that energy transduced through such conformational changes serves to release ATP from [7--17] and to promote productive binding of ADP and Pi to the enzyme [11-14, 17,18].…”
Section: Introductionmentioning
confidence: 99%